What strategies facilitate & support the successful transition of newly qualified midwives into practice: An integrative literature review. (November 2022) - Nolan, Samantha; Baird, Kathleen; McInnes, Rhona J.
Abstract: Objective: The aim of this review was to identify strategies that facilitate newly qualified midwives to transition successfully from midwifery student to confident, competent practitioner. Design: Integrative literature review. Data sources: The following databases were accessed: CINAHL complete, Medline complete, APA PsycINFO, Cochrane Library, Joanna Briggs Institute (JBI), Scopus and Google Scholar. Review methods: A systematic search of key terms across all data sources for the period January 1990 to September 2021 identified 316 papers whose titles/abstracts were screened against our inclusion/exclusion criteria. Thirty-six full texts were screened for eligibility and three papers were identified through ancestral searching. Ten papers were included in our final review. Results: Mentorship or preceptorship for newly qualified midwives by experienced midwives appears to enhance experiences, either as a standalone strategy, or component of structured programs of transition support. Supernumerary time, designated study days and planned rotations are also valued, particularly when rotating through clinical areas. Smaller teams providing continuity of midwifery care, or organisations that fund mentorship programs appear more able to facilitate support. Mechanisms of online support and learning may also enhance early transition but similarly, require organisational investment to aid success. Whilst most programs were described as helpful none of the studies used validated measures to assess this. Conclusion: Whilst elements of tailored support programs and mentoring/preceptorship from experienced colleagues appear to offer valuable support to transitioning practitioners, it is important to note that the structure of maternity care appears fundamental to the success of many of these strategies. Consequently, maternity care reform which focuses on the adoption of sustainable models of midwifery continuity, alongside urgent investment in midwives, are likely the most promising, over-arching strategies required to support student to midwife transition. Highlights: Newly qualified midwives often find their transition-to-practice year challenging. Investment in transition programs is vital to support newly qualified midwives. Validated tools are required to evaluate transition-to-practice programs.